Ce-Ni mixed oxide as efficient catalyst for H-2 production and nanofibrous carbon material from ethanol in the presence of water - Fang, Wenhao; Pirez, Cyril; Capron, Mickael; Paul, Sebastien; Raja, Thirumalaiswamy; Dhepe, Paresh Laxmikant; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (RSC Advances, 2012)
Hydrogen production from ethanol steam reforming (H2O/C2H5OH = 3) was studied over Ce-Ni based catalysts issued from different preparation methods (co-precipitation (CP), impregnation (IMP) and incipient wetness impregnation (IWI)). Catalysts prepared by the CP method exhibit higher activity and much better stability compared to the other two types of catalysts. The Ni1CeOY-CP catalyst is able to completely convert ethanol at 450 degrees C to H-2, CO2 and CH4 (almost no CO is observed), with a H-2 yield of 3 moles of hydrogen produced per mole of ethanol converted. A very high H-2 yield of 4.6 mol mol(EtOH)(-1) is achieved over the Ni1CeOY-CP mixed oxide at 650 degrees C. Correlations between the preparation method, catalytic activity and stability, and type of carbon deposition are discussed. The CP method forms very active small sized NiO (15 nm) and CeO2 (4 nm) nanoparticles, leading to the formation of a lower amount of carbon deposition in the form of nanofibrous carbon materials, the size of which depends on the Ni related nanoparticles. For CP catalysts, the graphitic filaments obtained correspond to carbon nanofibers (CNFs) and carbon nanotubes (CNTs) with a much smaller and homogenous size compared to the filamentous carbon formed over the catalysts issued from the other preparation methods, in relation to the active particles size. The catalytic stability is attributed to the type of carbon formed.

Controlling and stabilization of Ru nanoparticles by tuning the nitrogen content of the support for enhanced H-2 production through aqueous-phase reforming of glycerol - Gogoi, Pranjal; Kanna, Narsimharao; Begum, Pakiza; Deka, Ramesh C.; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (ACS Catalysis, 2020)
The stable activity of catalysts is an important issue in catalysis, particularly aqueous-phase reforming (APR) of renewable oxygenates, of biomass origin, to get H-2. Sintering of metal nanoparticles on supports affects catalyst stability. To alleviate this problem, a series of highly stable Ru-supported catalysts with controlled metal nanoparticle sizes have been prepared via the easy incipient wetness impregnation method. These catalysts were used for APR of glycerol to produce H-2. Nitrogen-doped mesoporous carbons (NMCs) were utlized as supports and found to have a strong influence on the catalytic performance of the catalysts. Incorporation of nitrogen in the carbon framework significantly enhanced the catalytic activity compared to Ru catalysts on nitrogen-free supports. Notably, the catalyst (5 wt % Ru-NMC-3) with optimal N content (10.9 wt %) demonstrated improved stability and H-2 selectivity, which are better than those of many state-of-the-art catalysts. Nitrogen in the carbon framework has a dual relationship with the activity of the catalyst: (i) it creates basic environment over the catalysts support and (ii) it acts as an anchoring site for metal nanoparticles. Anchoring of metal nanoparticles has helped to curb their sintering, thus leading to better stability of the catalysts under APR reaction conditions. Various characterization techniques were employed to understand the nature of active catalytic sites responsible for higher H-2 production while minimizing CO formation. In situ CO-FTIR studies showed that the higher catalytic activity of 5 wt % Ru-NMC-3 catalyst was attributed to the enhanced WGS activity over this catalyst. Density functional theory calculations were performed to understand the stabilization of metal nanoparticles by different types of N present on the support and provide insights into the prefered sites of glycerol adsorption on the NMC support. Since S wt % Ru-NMC-3 was the relatively best catalyst, it was selected for the preparation of bimetallic catalysts. Accordingly, addition of Pt to this system helped to increase the stability of the catalyst. This bimetallic catalyst may, therefore, find application for wide use in APR of biomass oxygenates.
Keywords: aqueous-phase reforming; Glycerol; H-2 production; Ru/NMC catalyst; synergistic effect

Comparative investigation on the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose - Manikandan, Marimuthu; Arjunan, Ayyappan; Prabu, Marimuthu; Raja, Thirumalaiswamy; Sangeetha, Palanivelu (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Hydrotalcites (HT) have a broad spectrum of applications as prosperous heterogeneous catalysts for diverse chemical transformations. The catalytic activity of HT-based materials can be tailored by introducing siliceous material into the internal or external framework. The surface modification of the HT framework with silica mesostructures leads to the formation of versatile Lewis base, Bronsted base and redox catalytic active sites. This work presents the comparative evaluation of the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose using 1-butanol as a solvent. The composites with different external morphology were prepared by a modified template-assisted hydrothermal method, using different HT to SBA-15 proportions. The textural and morphological characterization results conferred the efficiency of the employed post-synthetic intercalation strategy to achieve the successful formation of HT/SBA-15 and SBA-15/HT composites. With optimal HT loading and surface basicity, the HTS-3 composite demonstrated the highest catalytic performance, resulting in good glucose conversions (54 %) with improved selectivity (>83 %). The observed high reactivity could be mainly attributed to the extensive dispersion of HT particles on the SBA-15 component, which contributes to a significant increase in textural properties and surface basicity. Furthermore, special attention is devoted to addressing such reactivity phenomena as active site selectivity, catalyst multifunctionality and multisite reactivity commonly encountered in mesoporous catalysis.
Keywords: composites; glucose; hydrotalcite; isomerization; SBA-15

Co3O4 for sustainable CO2 reduction and possible fine-tuning towards selective CO production - Ranjan, Ravi; Tekawadia, Jyoti; Jain, Ruchi; Mhamane, Nitin B.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2023)
Two main challenges involved in heterogeneous catalytic CO2 reduction are: (a) decreasing the consumption of H2 to the minimum required level with possibly the maximum CO2 conversion, and (b) concurrently enhancing the selectivity of the desired CO, at the cost of methane. Towards meeting these two challenges, Co3O4 spinel has been identified as a potential catalyst and it exhibits predominant CO selectivity > 673 K at atmospheric pressure. CO2 conversion begins > 523 K, with 100% CO selectivity observed > 673 K with CO2:H2 = 3:2. Current work shows a sustainable catalytic CO2 conversion to 100% CO selectivity with Co3O4-Nanocube (NC). Critically, CO selectivity and yield is observed to increase at the cost of methane with smaller amount of H2. 1:1 and 3:2 CO2:H2 ratio exhibits 88-100% CO selectivity with 24-32.5% CO2 conversion between 623 and 823 K. Irrespective of the input CO2:H2, ratio of CO2:H2 uptake changes from around 1:3 at 523 K to 1:1-1.5 at 823 K with concurrent production of significant methane to predominant CO, respectively. Surface electronic state changes was explored by near ambient pressure photoelectron spectroscopy, and the results suggests that Co3O4 is the active phase that promotes CO2 reduction selectively to CO. Broadening observed with the vibrational feature of the CO2 molecules at high temperature underscores the heterogeneous character of the catalyst surface, under operating conditions, due to changing electron density. By optimizing the gas hourly space velocity (GHSV), H2-lean CO2:H2 ratio, and the reaction temperature/pressure, 100% CO selectivity could be broadened to a range of operating conditions.
Keywords: Carbon neutral economy; heterogeneous catalysis; RWGS; SDG; Surface Science